Kerjasama Industri Pertahanan melalui Pengadaan Jet Rafale untuk memperkuat Pertahanan Indonesia - Supono Hariyanto; Salim, Agus; Palupi, Endah (Journal of Industrial Engineering & Management Research, 2022)
The state must have qualified defence equipment as a means of protecting the state, both threats that come from within and from outside the country. Through defence equipment, the national branding of a country to other countries is used to show its power. For this reason, this study was written to know how the cooperative relationship between Indonesia and France is in the defence sector and how the steps taken by the two countries in increasing cooperation in the defence industry are. Indonesia needs fighter jets to rejuvenate its ageing defence equipment to protect and maintain the sovereignty of the Republic of Indonesia. The decision to choose the Rafale fighter jet produced by France has been through various considerations and calculations from stakeholders. This is in line with the National Actor Model Decision Making Theory proposed by Graham T. Allison, which analyses the cooperation between Indonesia and France. The method used in this research is descriptive analysis. This method applies to research written sources or literature studies. The data collection technique used is literature study, where the search for data comes from literary writing materials such as books, documents, mass media related to the problem. The results obtained from this study are that the two countries agreed to mutually enhance cooperation in the defence sector, this can be seen by encouraging the transfer of technology and knowledge, and the development of joint production of defence system tools between the two countries. Keywords: Defense Industry, Cooperation, Fighter Jets, Rafale